Internal Social Responsibility: an assessment based on official reporting data. - Zybareva, Oksana V.; Olena, Popadiuk; Yaskal, Ihor; Yaskal (Petrashchak), Oksana (My University, 2023)
The authors have suggested analytical tools to evaluate levels of internal social responsibility by developing an aggregate set of indicators. The reference indicators values were substantiated on the basis of average industry ones, which provided an opportunity to determine the multiple coefficients. The suggested tools provide the opportunity to define enterprises’ tendency for change in the level of responsibility level by years. This research can have important practical impacts due to its quantitative assessment having been based on published financial statements. The study creates additional opportunities for stakeholders to evaluate current internal corporate social responsibility levels and predict their own development direction.
Keywords: Corporate Social Responsibility (CSR), internal social responsibility, CSR metrics, financial statement, food industry enterprises